(untitled) (Proceedings of the International Conference on Public Health, 2022)
Since October 2021, there have been no reports of additional COVID-19 cases in Pikat Village. On January 21, 2022, a sick resident with symptoms of fever, headache, chest pain and shortness of breath was taken to Klungkung Hospital for treatment and PCR test results confirmed COVID-19. This investigation aims to evaluate the existence of an outbreak, describe the distribution and its risk factor. Descriptive design and case control were conducted immediately. Cases are residents with or without symptoms or close contacts with positive PCR tests and controls are close contacts with negative PCR results Data was collected using a questionnaire, and was analyzed univariate to multivariate. The index case is likely to be infected with COVID-19 while attending a massive traditional ceremony attended by many people from areas affected by COVID-19, 7 days before symptoms appeared. A total of 16 out of 17 (94.1%) close contacts of the index case were confirmed COVID-19. Tracing of 16 confirmed COVID-19 case showed that 5 out of 42 (11.9%) close contacts also confirmed as COVID-19. The proportion of male and female cases was balanced (54.5% vs. 45.5%), 50% were aged 20-60 years, and 68.2% lived in the index case area. The common symptoms of cases were runny nose/stuffy nose (50%) and cough (50%), but 40.9% were asymptomatic. Multivariable analysis showed that not wearing a mask when outside the house (OR=4.425; 95% CI 1.206-16.233), not keeping a distance (OR=3.69; 95% CI 1.012-13.480), and poor hand hygiene practice (OR=5.99; 95% CI 1.521-23.613) is a risk factor for being infected with COVID-19. It was concluded that there had been a COVID-19 cluster in Pikat Village triggered by reduced compliance with health protocols because they thought that COVID-19 is no longer existed. Socialization of health protocols is needed to prevent similar incidents.